Land-use and land-cover changes and their drivers in rangeland-dependent pastoral communities in the southern Afar Region of Ethiopia. Issue 1 (2nd May 2018) - Mekuyie, Muluken; Jordaan, Andries; Melka, Yoseph
Abstract : The present study was conducted in the southern Afar Region in Ethiopia to analyse the trends of land-use and land-cover changes and their drivers in the period 1985 to 2015 using remote sensing, field observation, focus group discussions and semi-structured interviews. A substantial loss of grassland cover (64.5%), moderate decline of cultivated land (24%) and a considerable increase in bush and shrub land cover (114.3%) occurred between 1985 and 2015. Consequently, pastoralist's access to rangeland resources and farmlands was highly restricted, thus putting the pastoral production system under increasing threat. A 13.3% decline of bare land was also observed during the same period. The results further indicated that policy, climate change, and variability, biotic factors including population growth, overgrazing, Prosopis juliflora seed dispersal via livestock's fecal droppings and seed germination potential of P. juliflora under moisture stress were the most important drivers of land-use and land-cover changes. Therefore, policy and strategies should be developed to control P. juliflora and give pastoralists full rights to their grazing land. Furthermore, there should be a strategy to strengthen the customary institution for effective management of rangeland resources.